Kewenangan Direktur Jenderal Perdagangan Dalam Negeri dalam Pembinaan Mengenai E-Commerce Terhadap Pelaku UMKM Pasar Tanah Abang Jakarta Pusat Berdasarkan Peraturan Menteri Perdagangan Republik Indonesia Nomor 31 Tahun 2023 Tentang Perizinan Berusaha, Periklanan, Pembinaan, dan Pengawasan Pelaku Usaha dalam Perdagangan Melalui Sistem Elektronik - Sri Ayuningsih, Meilani; Nurikah; Rayhan, Ahmad (Pratyaksa: Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2025)
The authority for guidance for MSME actors regarding e-commerce is regulated in the Regulation of the Minister of Trade of the Republic of Indonesia Number 31 of 2023 concerning business licensing, advertising, coaching, and supervision of business actors in trade through electronic systems. The problem arises due to the limited number of competent human resources in the field of e-commerce, especially in the Tanah Abang Market, Central Jakarta. The identification of problems in this study is how to implement the authority of the Directorate General of PDN in providing guidance to MSME Actors in the Tanah Abang Market, Central Jakarta in the context of developing e-commerce based on the Regulation of the Minister of Trade of the Republic of Indonesia Number 31 of 2023 and what are the supporting and inhibiting factors in the exercise of authority by the Directorate General of PDN in fostering e-commerce for MSME Actors in the Tanah Abang Market. The theories used are the theory of Authority and the theory of the Welfare State. Empirical juridical research method. The research specification used is descriptive analytical. The research data sources are in the form of primary and secondary data. Data collection techniques use field research techniques, literature research. The data analysis used was in the form of a qualitative descriptive approach. The results of the study show that the Directorate General of PDN has carried out various coaching efforts, such as training, mentoring, and facilitation of market access. However, the implementation of coaching still faces a number of challenges, such as resistance to change and lack of digital literacy, as well as limited infrastructure and human resources. The conclusion is that based on Article 43, the guidance carried out for PMSE is the authority of the Minister of Trade which is delegated to the Directorate General of PDN. Factors supporting the success of the coaching include government policy support, the existence of large market potential, and the availability of technological infrastructure. It is expected that the government should increase the strengthening of coordination and collaboration and the strengthening of mentoring and mentoring programs.